Emergency Medicine Case Study on Giant Cell Arteritis. (April 2023) - Vea, Davina L.; Hill, April T.
Abstract : The purpose of this case study on giant cell arteritis (GCA) is to ensure that emergency nurse practitioners (ENPs) are knowledgeable on this disease process to prevent serious complications such as permanent blindness in patients presenting to the emergency department (ED). The case study reviews emergency management of GCA, which includes diagnostic workup, pharmacological treatment, consults, disposition, follow-up care, and when to return to the ED. The classification criteria will be discussed for GCA from the American College of Rheumatology and the European Alliance of Associations for Rheumatology. In addition, risk assessment, clinical presentation, and physical examination findings will be listed. After reviewing this case study, ENPs should be able to identify GCA and manage care to reduce complications and recurrence of GCA in a patient presenting to the ED.